Improvement of Dyeing Efficiency of Direct Dyes on Cotton Fabric with Ozone - Jaroensappayanant, Phichitphol; Thammarong, Ravipa; Sittiprasong, Thanawat (Frontiers in Engineering Innovation Research, 2021)
Dyeing industry release high water pollution. Because of, there are a lot of dyestuffs and auxiliary remain in waste water which affect directly to the environment. The aim of this research is improvement of dyeing efficiency of direct dye on cotton fabric with ozone. The stimulate conditions such as ozone quantity, stimulation time and dyeing conditions such as sodium sulfate quantity ,dyeing temperature and time were study. The result was found that stimulation of dye liquor with ozone before dyeing can enhance dyeing efficiency of Ambidirect Red 8BL 180% and Direct Yellow S-XF. Stimulation with ozone 10-30 milligram per hour, at room temperature, for 10 minute. Then dyeing on cotton fabric by use 20 g/l sodium sulfate, at 60 ºC, for 20 minute. Indicate that, stimulation with ozone decrease sodium sulfate 50%, dyeing temperature 40ºC and time 20 minute. Because of higher K/S value. Color fastness testing was indicate that not effect to clocking fastness both dry and wet condition. Tearing strength also decrease.